Modelling thermochemical processes in protoplanetary discs I: numerical methods. Issue 3 (10th April 2020) - Grassi, T; Ercolano, B; Szűcs, L; Jennings, J; Picogna, G
ABSTRACT: The dispersal phase of planet-forming discs via winds driven by irradiation from the central star and/or magnetic fields in the disc itself is likely to play an important role in the formation and evolution of planetary systems. Current theoretical models lack predictive power to adequately constrain observations. We present prizmo, a code for evolving thermochemistry in protoplanetary discs capable of being coupled with hydrodynamical and multifrequency radiative transfer codes. We describe the main features of the code, including gas and surface chemistry, photochemistry, microphysics, and the main cooling and heating processes. The results of a suite of benchmarks, which include photon-dominated regions, slabs illuminated by radiation spectra that include X-ray, and well-established cooling functions evaluated at different temperatures, show good agreement both in terms of chemical and thermal structures. The development of this code is an important step to perform quantitative spectroscopy of disc winds, and ultimately the calculation of line profiles, which is urgently needed to shed light on the nature of observed disc winds.